Green technology approach for sustainable development: turning waste into useful bio-product - Alam, Md. Zahangir (2015)
There is no suitable and sustainable developed technology yet focused on process development and improvement to utilize the domestic and industrial residues (wastewaters) for value added applications. In addition, the world attention on this issue implicating that an environmental friendly system must be proposed as a green technology approach to convert these cheap organic renewable resources (substrates/raw materials) to valued bio-products. Extremely high content of degradable organic matter, carbohydrate and other nutrients in these resources enable it to serve as a good substrate/medium for microbial growth which might produce value added bio-products through bioconversion. In recent years, interest has twisted to the methods/processes based on resource recovery approach known as recovery, recycling and reuse of organic waste produced from different sources of domestic as well as industry. The concept of product recovery from residues by applying biological-based treatment is becoming more popular to be applied for various purposes. This paper highlights the overview of the researches on the ‘Turning waste into useful bio-products’, especially biofuels (bioethanol, biodiesel and biogas) and biocatalyst (enzymes) through green technology approach. Currently, various valued bio-products are developed from different sources of domestic and industrial wastes generated in Malaysia. The findings include sources and characteristics of domestic wastewater treatment plant (DWTP) sludge and oil palm industrial (OPI) waste in Malaysia. Results also show that bioconversion of DWTP sludge as biodegradation, settleability and dewaterability of treated sludge were highly influenced by the potential microbes isolated from the relevant source of wastes. Later, this novel concept is applied on bioconversion of various organic waste and turn them into several valued bio-products. The case studies on how the data of research and development (R&D) is scaled up to commercial level for resource recovery through bioconversion, reuse and recycling are presented in this paper.